2018
DOI: 10.1371/journal.pone.0208314
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of chicken peripheral blood lymphocyte in Taishan Pinus massoniana pollen polysaccharide regulation

Abstract: The natural polysaccharides extracted from the pollen of Pinus massoniana (TPPPS) have been shown to be a promising immune adjuvant against several viral chicken diseases. However, the exact mechanism through which TPPPS enhances the host immune response in chicken remains poorly understood. In the current study, chicken peripheral blood lymphocytes were treated with varying concentrations of TPPPS and pro-inflammatory cytokines such as IFN-γ, iIL-2 and IL-6 were measured to determine the optimal dose of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…CD4+ and CD8+ potentially play as cell-mediated immunity during the antibody synthesis and support to destruct the infected cells (Kempashi et al, 2017). The shrinkage of T cells subset in the lymphoid tissue dramatically changes the circulatory phenomenon not only in the haematological aspects but also the antibody synthesis (Yang et al, 2018).…”
Section: Dmentioning
confidence: 99%
“…CD4+ and CD8+ potentially play as cell-mediated immunity during the antibody synthesis and support to destruct the infected cells (Kempashi et al, 2017). The shrinkage of T cells subset in the lymphoid tissue dramatically changes the circulatory phenomenon not only in the haematological aspects but also the antibody synthesis (Yang et al, 2018).…”
Section: Dmentioning
confidence: 99%
“…Yang et al analyzed the effect of Taishan Pinus massoniana pollen polysaccharide on chicken peripheral blood lymphocyte proteome and identified 10 differentially expressed candidate proteins. Candidate proteins, and some differentially expressed proteins were associated with host innate immune response, stress-induced immune response and lipid synthesisrelated pathways (20). The intestine is the largest immune organ and contains a large number of immune cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that TPPPS can promote the proliferation and activation of poultry macrophages and enhance poultry resistance to pathogens by stimulating and activating lymphocytes and immunomodulatory functions by releasing cytokines IL-2 and TNF-α and increasing the chemical signaling mediator NO ( 65 ). Simultaneously, a proteomic study on peripheral blood lymphocytes of chickens treated with TPPPS showed that the differentially expressed proteins in the TPPPS group were related to host innate immune response and stress-induced immune response ( 66 ). The study also showed that in the model of poultry immunosuppression, TPPPS significantly enhanced the immune organ index of chickens, which enhanced the immune ability, promoted the differentiation and proliferation of CD4 + and CD8 + T lymphocytes, and significantly increased the levels of cytokines IL-2 and IFN-γ to mediate the immune response and enhance the immune system function of chickens ( 67 , 68 ).…”
Section: Plant Polysaccharidementioning
confidence: 99%